PENENTUAN WAKTU REAKSI DAN JUMLAH KATALIS (H2¬SO4 DAN KOH) OPTIMUM PADA PEMBUATAN BIODIESEL DARI MINYAK GORENG BEKAS - Abdullah Abdullah; Dorothy Eka Ria; Uripto Trisno Santoso; Kholifatu Rosyidah (Universitas Lambung Mangkurat, 2010)
Research of determination of optimum reaction time and number of catalyst (H2SO4 and KOH) at biodiesel production from waste cooking oil had been done. Aim of this research is to get the optimum reaction time and number of catalyst (H2SO4 and KOH), and the main chemical compound of biodiesel from waste cooking oil. Biodiesel from waste cooking oil is made from esterification reaction using H2SO4 2% w/w as acid catalyst, continued by transesterification reaction using KOH as base catalyst. The variables which is used in the research were the reaction time of esterification (45, 90, and 135 minutes) and transesterification (60, 120, and 180 minutes), while variation number of acid catalyst were 0,5; 1,0; 1,5 ml and base catalyst were 0,5; 1,0; 1,5 g. The optimum reaction time and number of catalyst were determined based on biodiesel characteristics are acid number, kinematics viscosity, and density. The characteristics were compared with waste cooking oil characteristic and SNI standard for biodiesel. Main chemical compound was determined by GC-MS instrument. Based on the research result obtained the optimum quality of methyl ester with acid number was 0,19 mg KOH/g, kinematics viscosity (40oC) was 4,51 mm2/s, and density was 0,875 g/ml. Concluded that the reaction time of esterification was 90 minutes and transesterification was 120 minutes, with number of catalyst H2SO4 2% w/w was 0,5 ml and KOH was 1,0 g for oil was 50 ml. Main chemical compound of biodiesel were methyl lauric, methyl myristic, methyl palmitic, and methyl oleic, respectively.